Lexical density and syntactic structure on Indonesian and Malaysian applied linguistics Scopus-indexed journal article titles - Jalilah, Elah; Asidiky, Zakie (JOALL (Journal of Applied Linguistics and Literature), 2025)
Writing research titles for academic or publication purposes is not easy. The features of titles can be observed in the amount of information they contain and how their structures convey meaning and achieve a particular purpose. Therefore, this study aimed to identify the lexical density level and syntactic structure use in titles of Indonesian and Malaysian Scopus-indexed journals in applied linguistics. It employed a descriptive qualitative research method to analyze 181 article titles using Ure’s (1971) theory of Lexical density and Cheng et al.’s (2012) theory of Syntactic structure. It used the data from the two most recent issues of four published journal articles: SIELE, 3L, IJAL, and GEMA. As a result, it shows that 181 titles fall within the range of very high, high, and medium levels of lexical density, with the very high level being the most dominant. Very high lexical density titles are packed with content words, making them highly information-rich. High lexical density titles also deliver precise information, fitting formal academic writing. Medium lexical density titles strike a balance between content and function words, making them less dense yet more approachable. Furthermore, the titles commonly use three syntactic structures: compound, nominal, and V-ing. The compound structure occurs the most in the data. The findings are expected to contribute to enriching the broader understanding of research title writing practices. Thus, it can be used as a reference for the writers to form the title.